Customary Land Registration in Practice: Lessons from Desa Adat Bangah, Indonesia - Maytha Puspa Dewi, Ni Luh Gede; Juwono, Vishnu (Universitas Teuku Umar, 2025)
Customary land registration remains a challenge in Indonesia’s agrarian policy. This study aims to analyze the implementation of the customary land registration policy in Desa Adat Bangah, Tabanan Regency, using the policy implementation framework. The research employs a descriptive qualitative approach through a literature review and policy document analysis. The findings indicate that the implementation of this policy is influenced by a combination of top-down and bottom-up factors, including policy standards, resource allocation, inter-organizational communication, the characteristics of implementing agencies, and the active participation of krama desa/customary law community (MHA). The successful registration of customary land in Desa Adat Bangah, marked by the issuance of four electronic certificates of management rights, demonstrates that Ministerial Regulation No. 14/2024 offers a solution to the challenges of customary land administration. However, this study also finds that the direct economic benefits for MHA require further examination. It recommends strengthening cross-sectoral coordination, enhancing the capacity of policy implementers, and refining regulations to ensure the sustainability and effectiveness of customary land registration policies in Indonesia.